Cognitive impairments in patients with subacute coronavirus disease: Initial experiences in a post-coronavirus disease clinic - Chang, Jhin Goo; Ha, Eun-Hye; Lee, Wangjun; Lee, Su Young (Frontiers in Aging Neuroscience, 2022)
Background: A significant number of patients experience persistent cognitive impairment after coronavirus disease (COVID-19) infection. This study aimed to investigate the cognitive function of patients in the subacute phase of COVID-19 and identify the clinical factors associated with cognitive sequelae. Methods: Data from patients who visited the psychiatric department of our post-COVID clinic between March and May 2022 were analyzed. The results of neuropsychiatric function tests, including digit span forward (attention/processing speed) and backward (working memory), trail making test part A (attention/processing speed) and part B (executive functioning), and Stroop word color interference test (executive functioning), and clinical data from 40 patients in the subacute phase of COVID-19 were finally analyzed. We calculated the frequency of impairments in each cognitive measure, defined as a z-score of ≤ 1.5 standard deviation below measure-specific age- and sex-adjusted norms. Results: Of the participants, 72.5% (n = 29) had impairments in at least one cognitive domain. Impairment in executive function was the most frequent (64.9%), followed by that in processing speed/attention (52.5%) and working memory (42.5%). Age was inversely correlated with the t-scores in all cognitive function tests. Conclusion: Regular examination of cognitive function is needed, especially in elderly individuals, regardless of the subjective symptom manifestations.